Methods of making variable‐rate nitrogen recommendations. Issue 6 (21st November 2016) - Arnall, Brian
Abstract : While a variable‐rate N strategy that works across all regions, landscapes, and cropping systems has yet to be developed, those methods that are capable of determining the three inputs of the Stanford equation while incorporating regional specificity will capture the greatest level of accuracy and precision. Earn 0.5 CEUs in Nutrient Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/811